Effect of the degree of hydrogenation on the viscosity, surface tension, and density of the liquid organic hydrogen carrier system based on diphenylmethane - Schmidt, Patrick; Kerscher, Manuel; Klein, Tobias; Jander, Julius Hans; Bioucas, Francisco; Rüde, Timo; Li, Shao; Stadelmaier, Monika; Hanyon, Samantha; Fathalla, Ramy; Bösmann, Andreas; Preuster, Patrick; et al. (International Journal of Hydrogen Energy, 2022)
For the efficient design of hydrogenation and dehydrogenation processes, a comprehensive database for the viscosity, surface tension, and density of mixtures of the diphenylmethane-based liquid organic hydrogen carrier system and the pure intermediate cyclohexylphenylmethane measured by complementary optical and conventional methods and calculated by molecular dynamics simulations at process-relevant temperatures up to 623 K is presented. The simulations employ self-developed force fields including a new one for cyclohexylphenylmethane and reveal surface enrichment and orientation effects influencing the surface tension. Relatively simple correlation and prediction approaches yield accurate representations as function of temperature and degree of hydrogenation (DoH) of the mixtures with average absolute relative deviations (AARD) of 0.07% for the density and 2.9% for the surface tension. Application of the extended hard sphere theory considering the presented accurate density data allows capturing the highly nonlinear DoH-dependent behavior of the dynamic viscosity with an AARD of 2.9%. (c) 2021 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Density; Experiment; LOHC mixtures; Modeling; Surface tension; Viscosity

PERFORMANCE OF BENZYLTOLUENE AS PURE HYDROCARBON LIQUID ORGANIC HYDROGEN CARRIER (LOHC) IN STORAGE CYCLES - Rüde, Timo; Preuster, Patrick; Wolf, Moritz; Wasserscheid, Peter (Proceedings of WHEC 2022 - 23rd World Hydrogen Energy Conference: Bridging Continents by H2, 2022)
This study presents benzyltoluene/perhydro benzyltoluene (H0-BT/H12-BT) as favourable liquid organic hydrogen carrier (LOHC) system for potential technical applications. LOHCs can enable safe and efficient hydrogen logistics using the existent fuel infrastructure. Compared with the well-established LOHC systems toluene/methylcyclohexane and dibenzyltoluene/perhydro dibenzyltoluene (H0-DBT/H18-DBT), the H0-BT/H12-BT system combines a similarly high volumetric storage density and excellent robustness in hydrogenation/dehydrogenation cycles with low viscosity for easy handling in colder operation conditions. Herein, we report repeated hydrogenation and dehydrogenation cycles of technical grade LOHCs in semi continuous operation at 290 °C with a commercial platinum on alumina catalyst (Pt/Al2O3). Reaction rates for both, hydrogen uptake and release, are generally found to be higher for H0-BT/H12-BT when compared to the DBT-based LOHC system at identical reaction conditions. By-product formation is low during cycling of the H0-BT/H12-BT system and only small amounts of the dehydrocyclisation products, such as methylfluorene species, are formed that can themselves act as hydrogen carrier.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Benzyltoluene; by-product formation; Chemical Hydrogen Storage; reaction rate; repeated storage cycles

Performance of Continuous Hydrogen Production from Perhydro Benzyltoluene by Catalytic Distillation and Heat Integration Concepts with a Fuel Cell - Rüde, Timo; Lu, Yanye; Anschuetz, Leon; Blasius, Marco; Wolf, Moritz; Preuster, Patrick; Wasserscheid, Peter; Geißelbrecht, Michael (Energy Technology, 2023)
The benzyltoluene-based liquid organic hydrogen carrier (LOHC) system enables the safe transport and loss-free storage of hydrogen. At least 26% of the lower heating value of the released hydrogen, however, has to be invested in form of heat to release the stored hydrogen. The low operation temperatures of catalytic distillation (CD) can facilitate waste heat integration to reduce external heat demand. Herein, the continuous hydrogen release from perhydro benzyltoluene via CD is demonstrated. It is revealed in the experimental results that this mode of operation leads to a high hydrogen release rate and very efficient noble metal catalyst usage at exceptionally mild conditions. The hydrogen-based productivity of platinum of 0.35 g(H2) g(Pt)(-1) min(-1) (0.7 kW(LHV_H2) g(Pt)(-1)) at a dehydrogenation temperature of only 267 degrees C is found to be nearly four times higher than for the conventional continuous liquid-phase dehydrogenation at the same temperature. Furthermore, simulation results of the CD process are described. The feasibility of a fully heat-integrated process for electricity generation from the released hydrogen via CD using waste heat from the fuel cell for the CD reboiler is demonstrated. The technical potential of coupling the H12-BT dehydrogenation by CD with high-temperature fuel cell operation is highlighted by the simulation.
CRIS-Team WoS Importer:2023-02-24

Resilience of LOHC Based Energy Storage Systems - Rüde, Timo; Bösmann, Andreas; Preuster, Patrick; Wasserscheid, Peter; Arlt, Wolfgang; Müller, Karsten (Energy Technology, 2017)

Viscosity, surface tension, and density of the liquid organic hydrogen carrier system based on diphenylmethane, biphenyl, and benzophenone - Jander, Julius Hans; Kerscher, Manuel; Cui, Junwei; Wicklein, Johannes; Rüde, Timo; Preuster, Patrick; Rausch, Michael Heinrich; Wasserscheid, Peter; Koller, Thomas Manfred; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2022)
Keywords: Biphenyl; Liquid organic hydrogen carrier; Surface tension; Diphenylmethane; Eutectic mixture; Viscosity